Interface between Intellectual Disability and Mental Health: hermeneutic review - Surjus, Luciana Togni de Lima e Silva; Campos, Rosana Teresa Onocko (Revista de Saúde Pública, 2014)
A literature review was conducted aiming to understand the interface between the Intellectual Disability and Mental Health fields and to contribute to mitigating the path of institutionalizing individuals with intellectual deficiencies. The so-called dual diagnosis phenomenon remains underestimated in Brazil but is the object of research and specific public policy internationally. This phenomenon alerts us to the prevalence of mental health problems in those with intellectual disabilities, limiting their social inclusion. The findings reinforce the importance of this theme and indicate possible diagnostic invisibility of the development of mental illness in those with intellectual disabilities in Brazil, which may contribute to sustaining psychiatric institutionalization of this population.